Погляд на сьогодення і майбутнє експрес-контролю виробництва сталі - Азаренков, Є.А. (Physico-technological Institute of Metals and Alloys, 2023)
In this article, based on the author's many years experience in the leading global company Heraeus Electro-Nite, which produces measuring instruments for various parameters of liquid metals during their production, it is summarised the current state of things and trends in this matter. The vision of the development of analytical control of steel production, outlines the contours of a possible solution, initiating significant progress in this matter is formulated. The implementation of the proposed concept could open new areas of technology, particularly in the spectrometry of metals, in organization of technological processes of their production. Despite the continuous improvement of equipment used to perform analytical control of metal at various sites of the “redistribution”, for several decades, the structure of the organization of control and the arrangement of the measuring instruments themselves have remained unchanged. Instead of operators manually measuring with probes in the form of fishing rods, on which measuring sensors or samplers are worn, manipulators are increasingly being used. However, the basic design of the sensors themselves remains unchanged: a protective cardboard sleeve plus a measuring element or a sampler head. Measurements are made periodically, lasting from several to tens of seconds, after which the sensor (sampler), having performed one measurement (in the case of the sampler, having obtained a metal sample), fails. For the next measurement, another probe is put on the probe, etc. Since, apparently, qualitative changes have ripened in the implementation of routine analytical control, a lot of research and development has been devoted to finding solutions to exclude sampling from the analytical control of steel production. In this article the author is describing one of the possible solutions to this super-task – usage of optical spectrometer together with set of equipment that provide the excitation of characteristic radiation of analyzed liquid steel and transferring it to the spectrometer.